Palaeeudyptes klekowskii, the best-preserved penguin skeleton from the Eocene-Oligocene of Antarctica: taxonomic and evolutionary remarks - Acosta Hospitaleche, Carolina Ileana Alicia (2014)
A new fossil penguin skeleton from the La Meseta Formation collected at the locality DPV 13/84 (Seymour Island, Antarctic Peninsula) from the crinoid horizon located 40 m above the base of the 145 m-thick Submeseta Allomember (Late Eocene–Early Oligocene?) is described. The specimen is assigned to the species Palaeeudyptes klekowskii Myrcha, Tatur and del Valle, 1990; it is the most complete penguin skeleton ever recovered from Antarctica. Discoveries like this one are significant for the study of the anatomy and evolution of penguins, in particular regarding the Antarctic species included in the genus Palaeeudyptes Huxley, 1859. P. klekowskii closely resembles its smaller congeneric species P. gunnari (Wiman, 1905), with only the relative concavity of the margo medialis distinguishing the tarsometatarsi of both taxa. However, the results of a geometric morphometric analysis show some intra- and inter-specific variations, making possible the systematic assignment of the majority of the specimens. Size variation is congruent with the presence of two different species.